Progressive Cenozoic cooling and the demise of Antarctica’s last refugium - Anderson, John B. (National Academy of Sciences, 2011)
The Antarctic Peninsula is considered to be the last region of Antarctica to have been fully glaciated as a result of Cenozoic climatic cooling. As such, it was likely the last refugium for plants and animals that had inhabited the continent since it separated from the Gondwana supercontinent. Drill cores and seismic data acquired during two cruises (SHALDRIL I and II) in the northernmost Peninsula region yield a record that, when combined with existing data, indicates progressive cooling and associated changes in terrestrial vegetation over the course of the past 37 million years. Mountain glaciation began in the latest Eocene (approximately 37–34 Ma), contemporaneous with glaciation elsewhere on the continent and a reduction in atmospheric CO(2) concentrations. This climate cooling was accompanied by a decrease in diversity of the angiosperm-dominated vegetation that inhabited the northern peninsula during the Eocene. A mosaic of southern beech and conifer-dominated woodlands and tundra continued to occupy the region during the Oligocene (approximately 34–23 Ma). By the middle Miocene (approximately 16–11.6 Ma), localized pockets of limited tundra still existed at least until 12.8 Ma. The transition from temperate, alpine glaciation to a dynamic, polythermal ice sheet took place during the middle Miocene. The northernmost Peninsula was overridden by an ice sheet in the early Pliocene (approximately 5.3–3.6 Ma). The long cooling history of the peninsula is consistent with the extended timescales of tectonic evolution of the Antarctic margin, involving the opening of ocean passageways and associated establishment of circumpolar circulation.